A colorimetric and fluorometric dual-modal DNA logic gate based on the response of a cyanine dye supramolecule to G-quadruplexes. (14th January 2016) - Chen, Hongbo; Sun, Hongxia; Zhang, Xiufeng; Sun, Xiaoran; Shi, Yunhua; Xu, Shujuan; Tang, Yalin
Abstract : The INHIBIT DNA logic gate with dual-modal outputs based on the response of MTC aggregates to G-quadruplexes. Abstract : A colorimetric and fluorometric dual-modal DNA logic gate has been constructed, which is based on the response of a cyanine dye supramolecule to K + –Pb 2+ -switched G-quadruplexes. Only when the input is K +, the output is 1, which made the system an INHIBIT logic gate. The gate operation constructed here is label-free, and is of simple design and low-cost, showing great promise for practical onsite applications.